2018
DOI: 10.1007/s11356-018-1870-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of arsenic(III) from aqueous media using magnetic polyaniline-doped strontium–titanium nanocomposite

Abstract: In this study, a novel nanocomposite adsorbent based on magnetic polyaniline and strontium-titanium (MP-SrTiO) nanoparticles was synthesized via a simple and low-cost polymerization method for efficiently removing of arsenic(III) ions from aqueous samples. The chemical structure, surface properties, and morphology of the prepared adsorbent were studied using Fourier transform infrared spectroscopy (FTIR), energy-dispersive X-ray spectroscopy (EDX), and scanning electron microscopy (SEM). The main effective par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Figure 8 shows that both PANi and the composite 70%PANi-30%ZnO were more effective than the other materials even at 0.05 g/L (i.e., lowest dosage) with a removal ratio of almost 100%. The treated PANi and the other composites material showed a signi cant increase in the removal of MO with the increase in the adsorbent dose (0.05-0.2 g), similar to previous researchers who reported that Polyaniline and its modi ed forms have been effective adsorbents for the adsorption of dyes and heavy metals [47][48][49][50].…”
Section: Effect Of Materials Dose On the Absorbancesupporting
confidence: 87%
“…Figure 8 shows that both PANi and the composite 70%PANi-30%ZnO were more effective than the other materials even at 0.05 g/L (i.e., lowest dosage) with a removal ratio of almost 100%. The treated PANi and the other composites material showed a signi cant increase in the removal of MO with the increase in the adsorbent dose (0.05-0.2 g), similar to previous researchers who reported that Polyaniline and its modi ed forms have been effective adsorbents for the adsorption of dyes and heavy metals [47][48][49][50].…”
Section: Effect Of Materials Dose On the Absorbancesupporting
confidence: 87%
“…This indicates that the metal oxide (M–O) nanoparticles were successfully introduced. Lastly, the absorption peak (1,704 cm −1 ) ascribed to the metal–carbonyl (OM–C=O) link indicating the successful assemblage of MO nanoparticles and GO sheets 29 …”
Section: Resultsmentioning
confidence: 99%
“…The use of PANI-clay hybrid materials for the removal of Cu (II) was reported by [37]. Additionally, removal of arsenic (III) ions by magnetic polyaniline doped-strontium titanium nanocomposites adsorbent were reported by [38]. The maximum adsorption capacity was found to be 67.11 mg/g from the Langmuir isotherm model, and the nature of the adsorption process of arsenic (III) ions was found to be exothermic and physisorption deduced from the thermodynamic studies.…”
Section: Pani and Pani-based Composite Adsorbents For The Removal Of Heavy Metal Ions (Hmis)mentioning
confidence: 99%